2008
DOI: 10.1164/rccm.200708-1248oc
|View full text |Cite
|
Sign up to set email alerts
|

Reference Ranges for Spirometry Across All Ages

Abstract: Rationale: The Third National Health and Nutrition Examination Survey (NHANES III) reference is currently recommended for interpreting spirometry results, but it is limited by the lack of subjects younger than 8 years and does not continuously model spirometry across all ages. Objectives: By collating pediatric data from other large-population surveys, we have investigated ways of developing reference ranges that more accurately describe the relationship between spirometric lung function and height and age wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
777
2
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 635 publications
(803 citation statements)
references
References 21 publications
17
777
2
7
Order By: Relevance
“…BPD, bronchopulmonary dysplasia; EP, subjects born extreme preterm (ie, gestational age ≤28 weeks or birth weight ≤1000 g); FEF , forced expiratory flow at 25-75% of FVC; FEV 1 , forced expiratory volume in 1 s; FVC, forced vital capacity; m/s BPD, moderate/severe BPD (ie, oxygen supplement at gestational age 36 weeks); mild BPD, oxygen supplement at 28 postnatal days; z Score, (observed value − expected value)/(SE of the expected value), calculated with the all-age reference equation. 17 the NICU. Subjects were retrospectively included in 2001, but the organisation of medical care in the region and identical algorithms for determination of gestational age at birth ensured that recruitment would have been the same if performed prospectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BPD, bronchopulmonary dysplasia; EP, subjects born extreme preterm (ie, gestational age ≤28 weeks or birth weight ≤1000 g); FEF , forced expiratory flow at 25-75% of FVC; FEV 1 , forced expiratory volume in 1 s; FVC, forced vital capacity; m/s BPD, moderate/severe BPD (ie, oxygen supplement at gestational age 36 weeks); mild BPD, oxygen supplement at 28 postnatal days; z Score, (observed value − expected value)/(SE of the expected value), calculated with the all-age reference equation. 17 the NICU. Subjects were retrospectively included in 2001, but the organisation of medical care in the region and identical algorithms for determination of gestational age at birth ensured that recruitment would have been the same if performed prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…16 Forced expiratory volume in 1 s (FEV 1 ), forced vital capacity (FVC) and forced expiratory flow at 25-75% of FVC (FEF ) were recorded and standardised to z scores and percentages of predicted using the all-age reference equation, correcting raw data for differences in age, sex and height. 17 …”
Section: Lung Function Measurementsmentioning
confidence: 99%
“…(10) TEF patients with a history of GERD were more likely to have pulmonary function abnormalities and many authors have suggested that GERD in the first years after TEF repair may play a major role in TEF-associated pulmonary pathology. (7;8;11-13) The purpose of this study was to assess the influence of GERD on pulmonary function and exercise capacity in a group of patients aged [8][9][10][11][12][13][14][15][16][17][18] years, who had undergone neonatal surgical repair of TEF. We categorized TEF in two groups: those who had undergone anti-reflux surgery (and consequently were considered to have had severe GERD (s-GERD)) and those who had not (considering to have had mild GERD).…”
mentioning
confidence: 99%
“…The disappearance of synovial joints between the sternum and the costal cartilages decreases the chest-wall compliance and tension forces, with consequent decrease in maximal respiratory pressure and hypotrophy of accessory respiratory muscles [7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
“…These changes, associated with respiratory infections and frequent exposure to stressors, such as toxic particles from the environment and smoking, can lead to airflow limitation, which is defined by a decrease in the ratio between forced expiratory volume (FEV 1 ) and forced vital capacity (FVC), and may be accompanied by an increase in residual volume and functional residual capacity [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%